The Tobacco Beetle in Egyptian Mummies by Dominique Görlitz - Jett, Stephen C. (Journal of Scientific Exploration, 2013)
Dominique Görlitz is a German experimental archaeologist specializing in ancient watercraft trials. He here reviews the evidence concerning the presence of tobacco leaves, residues of nicotine and cocaine, and tobacco beetles in the tombs/mummies of the ancient Egyptian Pharaohs Ramses II and Tutankhamen. In this article, he contributes valuable information and observations additional to what is covered in this editor's earlier works (see Jett articles, Pre-Columbiana 2(4) and 3(1-3), of which Görlitz appears to be unaware). While a French team was restoring Ramses's mummy during the 1970s, it discovered shredded Nicotiana sp. leaves in the lowest parts of the abdominal cavity. The tobacco was part of a homogeneous mixture of finely chopped plants of various kinds, surrounded by the resins of embalmment. There was also nicotine in the wrappings-on which also appeared an imago of a tobacco beetle, Lasioderma serricorne. Like domesticated tobacco, this beetle is believed to be of New World origin. The tobacco-fragment samples were obtained with long biopsy tweezers from inaccessible sites through previously made artificial openings, seemingly obviating the possibility of contamination or of nineteenth-century insertion. The relevant material cannot at present be carbon dated, because the sample in Paris has disappeared. Later, a team led by the Munich forensic pathologist Svetlana Balabanova detected residues of nicotine in other ancient and medieval Egyptian mummies, finding greater concentrations of the alkaloid and/or its metabolites in artificially mummified cadavers than in naturally desiccated ones. This suggests deliberate use of Nicotiana as an antiputrefactant in the mummification process, in addition to ingestion. Certain other Old World plants-including solanaceous species, sour cherry, common polypody, and stonecrop-carry nicotine, but in concentrations too slight to account for the mummies' concentrations.